Philosophical Management of Stress based on Science and Epicurean Pragmatism: A Pilot Study - Yapijakis, Christos; Protopapadakis, Evangelos D.; Chrousos, George P. (Conatus - Journal of Philosophy, 2022)
In the first months of the COVID-19 pandemic, we created and implemented from November 2020 to February 2021 a monthly educational pilot program of philosophical management of stress based on Science, Humanism and Epicurean Pragmatism, which was offered to employees of 26 municipalities in the Prefecture of Attica, Greece. The program named “Philosophical Distress Management Operation System” (Philo.Di.M.O.S.) is novel and unique in its kind, as it combines a certain Greek philosophical tradition (Epicurean) that concurs with modern scientific knowledge. The program was designed to be implemented in a period of crisis; therefore, it used a fast-paced, easy to learn and practice philosophical approach to stress management, based on cognitive psychotherapy. The philosophical approach to stress management has the advantage that it can be offered to most people, regardless of age and educational level. The pilot program was effective in achieving its objectives, shown by statistical comparisons of the trainees’ responses to anonymous questionnaires before and after the month-long training. The successful Philo.Di.M.O.S. program, thus, based on a solid scientific and philosophical basis, offers a paradigm of stress management during crises and could be useful in Greece and internationally.